The Irrational number: a historical view teaching (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The study presented was realized by the intention of studying: (1) from a historical standpoint epistemological evolution of the concept of irrational number, (2) from an educational point of view, teaching the concept of irrational number across the curriculum and textbooks. Just the first purpose is shown in this work. Among the findings are four conceptual frameworks in its epistemological sense: the irrational associated among reasons; associated to the arithmetic; associated with an approximation of a close rational number; and the irrational associated with a number.
Keywords: irrational number; epistemological conceptual frameworks; historical evolution